Continuous aqueous phase reforming of a synthetic brewery wastewater with Pt/C and PtRe/C catalysts for biohydrogen production. (October 2021) - Oliveira, A.S.; Cordero-Lanzac, T.; Baeza, J.A.; Calvo, L.; Heras, F.; Rodriguez, J.J.; Gilarranz, M.A.
Abstract: This work investigates H2 production through aqueous phase reforming (APR) of synthetic brewery wastewater in a continuous fixed bed reactor with Pt and PtRe (3 wt %) catalysts supported on activated carbon. The influence of weight hourly space velocity (WHSV) and superficial Ar gas flow velocity (VAr ) was assessed for the sake of optimisation, while reaction temperature and pressure were maintained at 225 °C and 28 bar, respectively. H2 production was found to be higher using the PtRe catalyst at the lowest WHSV (0.03 h −1 ) and highest VAr (0.8 cm s −1 ). The comparison of the maximum H2 production obtained in this work (27.9 μmol min −1 ) with other treatment processes shows the potential of the application of APR process for H2 production from brewery wastewater. Despite the different reaction conditions tested, the catalysts showed deactivation with time on stream, which was related to the formation of solid deposits on the surface of the catalysts. Therefore, future research should be related to the development of more stable catalysts, strategies that avoid deactivation by coking and regeneration processes. Graphical abstract: Image 1 Highlights: PtRe catalyst yielded higher activity and H2 production than the Pt one. H2 production increased as WHSV decreased, due to longer contact time. H2 production increased as V Ar increased due to lower consumption in side reactions. Catalyst deactivation was observed due to the formation of carbonaceous solids. A residual H2 production was maintained upon TOS, most probably related to HTC.